Peningkatan Partisipasi Dan Minat Belajar Geografi Melalui Pendekatan Game-Based Learning Pada Peserta didik - Siahaan, Rikalayasi; Arent, Ease; Haloho, Bongguk (Jurnal Penelitian dan Pendidikan IPS, 2024)
This study aims to increase participation and interest in learning geography in students of class XI Social 1 at Private High School Abdi Sejati Commerce through the Game-Based Learning approach on biosphere materials. The method used is Classroom Action Research (PTK) with two cycles, involving 30 students. The results showed that 93.33% of students found the geography learning carried out very interesting, and 86.67% agreed that the Game-Based Learning method could be applied to other subjects. The average achievement of learning scores increased from 55 in the initial condition to 81.46 in the second cycle. In addition, the presentation of students' learning interests also increased from 50% to 93.33%. These findings indicate that Game-Based Learning type cooperative learning strategies are effective in increasing students' interest and learning outcomes, as well as fostering the ability to cooperate and think critically